NEGARA DAN GOLKAR (Studi tentang Konfigurasi Politik Indonesia 1971-2009) - Sudjito, Gatot (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
The study aims to answer the question of how: (1) political configuration that putsIndonesia in 1971-1997 Golkar as a single force (2) political configuration in 1998 thatcaused the New Order government fell, and (3) the political configuration in 1999-2009resulting Golkar political disorientation. The results: (1) the political configuration ofIndonesia in 1971-1997 accidentally put Golkar as a single force on the grounds that thegovernment can carry out the construction with smooth and stable. Sekber-military formwith the government, Golkar then follow the 1971 general election and won an absoluteacquire 62.82% of the vote. Thanks to that victory, Golkar and the military dominatedparliament. Various attempts were made by the government in order to Golkar remains asingular force that harm the PPP and PDI, the result, until the 1997 election Golkar alwayswins absolute; (2) As a result of the New Order regime always manipulate the orderabsolute win Golkar, the public is not satisfied, the scent of corruption in the preparation ofDevelopment Cabinet VII concurrent multi-dimensional crisis of 1997 to encourage peopledemanded a change in many lives. The insistence of the President submit his cause to B.J.Habibie to date May 21, 1998. Since then New Order, (3) After the fall of the New Order,Golkar as also fell. With the remnants of the existing resources can Golkar following the1999 elections, the results dropped dramatically compared to the 1997 election due to: (1)Chairman of the Board of Trustees of the New Order era Golkar political structure intactbequeath to future generations, (2) the Golkar elite divisions; (3) the loss of support of themilitary and civil servants, (4) a more competitive electoral policies, (5) the division ofvoters into 47 political parties, (6) the emergence of a new reformist parties. The successof the Golkar Party in the 2004 elections resulting from the internal side: (1) the GolkarParty fought a modern and independent party, (2) political machine that has formedrevived; (3) more democratic, (4) the persistence of traditional voters, and (5 ) personalfactors Akbar. Of external factors as: (1) some people miss the New Order government andreselect the Golkar Party, (2) Some supporters of the PDIP in the 1999 elections Golkar.Keywords: state, Golkar, political configuration.